The Impacts of Smartphones on Early Childhood Language Development - Nurmalina Nurmalina; Deddy Gusman (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims at determining the impact of using smartphones on aspects of early childhood language development. This analytical descriptive study was conducted among early childhood children. Documentation was the technique for collecting the data whereas analysing the data was the library research method. Allowing children to use smartphones which are still at an early age with adequate time control, does not interfere with their language development. Children with these criteria can still develop normally. However, the undesirable effects of using smartphones outweigh the constructive effects. In conclusion, early childhood is already familiar with smartphones and is strongly dependent on them in their activities. With a high quantity of time, children’s language development is not optimal and tends to be hampered.